A 50% increase in the terbium-based OLED luminance through reducing the excited-state lifetime due to the introduction of gold nanoparticles - Gladkikh, Arseny Yu; Kozlov, Makarii I; Vashchenko, Andrey A; Medved'ko, Aleksei V; Goloveshkin, Alexander S; Bolshakova, Anastasia V; Latipov, Egor V; Utochnikova, Valentina V (Dalton transactions : an international journal of inorganic chemistry, 2022)
An increase in the efficiency for a terbium-based OLED was achieved by introducing gold nanoparticles into the PEDOT:PSS hole injection layer and was mainly due to the improvement in carrier injection and the reduction of the excited-state lifetime. The introduction of plasmon-resonant gold nanoparticles resulted in a 50% increase in the Tb(czb) 3 TDZP luminance, which reached 480 cd m −2 and is the highest result for OLEDs based on aromatic carboxylates. The first study of the gold nanoparticles introduction into the lanthanide-based OLED demonstrated a 50% increase in the luminance of terbium-based OLED. This effect was proved to be due to the decrease in the excited state lifetime.